Climate and sea‐level controlling internal architecture of a Quaternary carbonate ramp (Northwest Shelf of Australia). Issue 3 (22nd October 2021) - Hallenberger, Maximilian; Reuning, Lars; Back, Stefan; Gallagher, Stephen J.; Iwatani, Hokuto; Lindhorst, Katja
Abstract: The continental shelf of Northwest Australia hosts an extensive tropical carbonate ramp that forms an important template for the interpretation of similar systems in the sedimentary record. Yet, little is known about its development from the middle to late Quaternary, a period of high frequency glacioeustatic changes in sea‐level and climate. This research describes core and seismic‐reflection data from a mid‐ramp to outer ramp transect at the Northwest Shelf. Core material includes the upper 70 m of International Ocean Discovery Program Site U1461 (Expedition 356), which covers the last 500 kyr. During arid glacials, sedimentation is characterized by inorganically precipitated carbonates, including aragonite‐needle mud and ooids. Ooids developed under shallow marine conditions on small‐scale flat‐topped platforms. Seismic and sedimentological evidence indicates that these platforms developed locally on top of the present‐day mid‐ramp and were typically only active during a single glacial period. Aragonite‐needle mud precipitated (inorganically) in shallow‐water areas. Much of these fine sediments were subsequently exported into deeper water where they mixed with pelagic carbonates. Humid interglacials are generally characterized by reduced sedimentation across the Northwest Shelf of Australia, resulting in the amalgamation of glacial lowstand deposits. Yet, substantial amounts of skeletal carbonates were deposited at the studied location during the Holocene and Marine Isotope Stage 11. These sediment accumulations are interpreted as a local feature caused by a decline in current energy. The study presented highlights a ramp system where climate is as important as sea‐level in controlling carbonate deposition.